FORMULASI DAN UJI EVALUASI FISIK SEDIAAN GEL PEEL-OFF SEBAGAI MASKER WAJAH DARI SARI WORTEL (DAUCUS CAROTA L.) - Alensia Putri, Nofellia; Dwiningrium, Riza; Suswidiantoro, Vicko; Pratiwi, Mida (Jurnal Riset Kefarmasian Indonesia, 2025)
Carrots (Daucus carota L.) are rich in beta-carotene, vitamins A, C, and E, which possess antioxidant activity and potential for use as active ingredients in cosmetic formulations. This study aimed to formulate and evaluate the physical characteristics of peel-off gel mask preparations containing carrot juice at varying concentrations. A laboratory-based experimental design was used to develop three formulations containing 5 %, 10 %, and 15 % carrot juice. Physical evaluations included organoleptic properties, homogeneity, pH, drying time, spreadability, adhesiveness, protective effect, and skin moisture. All formulations demonstrated acceptable physical stability. The 10% concentration formula showed the most ideal drying time, balanced spreadability and adhesiveness, and the most significant increase in skin moisture. These findings indicate that carrot juice can be effectively used as a single active ingredient in peel-off gel mask formulations, with 10 % identified as the most optimal concentration. For future development, further studies are recommended to include long-term stability testing, dermatological evaluations on human subjects, and exploration of combinations with other natural ingredients to enhance effectiveness and support broader applications in herbal-based cosmetic industries.